2020
DOI: 10.1038/s41419-020-2638-2
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2 is dispensable for photoreceptor development but is required for survival during aging and outer retinal stress

Abstract: Photoreceptor death is the ultimate cause of vision loss in many retinal degenerative conditions. Identifying novel therapeutic avenues for prolonging photoreceptor health and function has the potential to improve vision and quality of life for patients suffering from degenerative retinal disorders. Photoreceptors are metabolically unique among other neurons in that they process the majority of their glucose via aerobic glycolysis. One of the main regulators of aerobic glycolysis is hexokinase 2 (HK2). Beyond … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 56 publications
4
41
1
Order By: Relevance
“…We crossed RHO-Cre mice with HK2-floxed mice to selectively knock down HK2 in rods, with age-matched HK2 wild-type (WT) mice serving as controls. As previous studies found limited retinal changes around 5 months after disruption of glycolysis 13 , 14 , 19 , we characterized changes in the retina in two groups of mice: young mice at 19~20 weeks and aged mice 40~41 weeks of age. We used 4 retinas from individual mice per group for Western blots on each polyvinylidene difluoride (PVDF) membrane, 4 eyes/group for immunohistochemistry (IHC) on frozen sections, 8 mice/group for electroretinography (ERG), optical coherence tomography (OCT) and 7–8 retinas/group for metabolic analysis, in the study as described below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We crossed RHO-Cre mice with HK2-floxed mice to selectively knock down HK2 in rods, with age-matched HK2 wild-type (WT) mice serving as controls. As previous studies found limited retinal changes around 5 months after disruption of glycolysis 13 , 14 , 19 , we characterized changes in the retina in two groups of mice: young mice at 19~20 weeks and aged mice 40~41 weeks of age. We used 4 retinas from individual mice per group for Western blots on each polyvinylidene difluoride (PVDF) membrane, 4 eyes/group for immunohistochemistry (IHC) on frozen sections, 8 mice/group for electroretinography (ERG), optical coherence tomography (OCT) and 7–8 retinas/group for metabolic analysis, in the study as described below.…”
Section: Methodsmentioning
confidence: 99%
“…HK1 is found in all mammalian tissues and considered as a “housekeeping enzyme” in physiological conditions. HK2 is the isoform that is highly expressed in photoreceptors 15 , 19 . HK1 and HK2 can associate with voltage-dependent-anion channel (VDAC) to regulate mitochondrial function 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, the RPE expresses remarkably high levels of GLUT1 at their apical and basolateral surface (164). Glucose in the cytosol would normally be quickly converted for its use in glycolysis, but this is effectively suppressed in the RPE by the lactate that is produced and exported by the photoreceptor and because kinases that act on sugars are inhibited or expressed at sufficient low levels (164,165). Conversely, such kinases (e.g.…”
Section: Recycling Between the Rpe And Photoreceptorsmentioning
confidence: 99%